Whole‐genome sequencing of cell‐free DNA reveals DNA of tumor origin in plasma from patients with colorectal adenomas - Amanda Frydendahl; Adam J. Widman; Nadia Øgaard; Anushri Arora; Daniel Halmos; Jesper Nors; Johanne Ahrenfeldt; Tenna V. Henriksen; Christina Demuth; Line Raaby; Mads H. Rasmussen; Christina Therkildsen; et al. (Molecular Oncology)
The presence of circulating tumor DNA (ctDNA) in patients with colorectal adenomas remains uncertain. Studies using tumor‐agnostic approaches report ctDNA in 10–15% of patients, though with uncertainty as to whether the signal originates from the adenoma. To obtain an accurate estimate of the proportion of patients with ctDNA, a sensitive tumor‐informed strategy is preferred, as it ensures the detected signal originates from the adenoma. Here, tumor‐informed whole‐genome sequencing‐based ctDNA analysis (MRD‐EDGESNV) was applied to two independent cohorts. Cohort 1, comprising 93 patients with stage III colorectal cancer (CRC) and 40 healthy individuals, was used to establish the signal threshold at 95% specificity. This threshold was then applied to Cohort 2, consisting of 22 patients with symptomatic and 20 with asymptomatic adenomas. In stage III, MRD‐EDGESNV had an area under the curve of 0.98. ctDNA was detected in 50% and 25% of patients with symptomatic and asymptomatic adenomas, respectively. The median adenoma plasma tumor fraction was 5.9 × 10−5. These finding not only demonstrate the feasibility of ctDNA detection in patients with colorectal adenomas, but also provides an estimate of the necessary sensitivity required to detect these lesions, paving the way for future ctDNA‐based screening strategies.